Penggunaan Media Pembelajaran Digital dalam Meningkatkan Kualitas Pendidikan : Studi Kasus Di Pondok Pesantren Al Azhar Muncar - Siti Nurhaliza Hertiani; Ahmad Rifqi Luthfiansyah; Devita Hendriyanti; Adam Ibrahim Hafiz; Fadylah Annisa; Faqih Fuadi Lahfi (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study is to examine how the Al Azhar Muncar Islamic Boarding School in Banyumas Regency, East Java, uses digital learning resources to raise the standard of instruction. Primary data from observations and interviews with managers, students, and teaching staff of Islamic boarding schools, as well as secondary data from digital documents and artifacts, comprise the qualitative case study research methodology. It is anticipated that the study's findings would reveal the kinds of digital media that are utilized, how well they aid in learning, and what variables facilitate or hinder their use. In order to optimize the use of digital technology in the context of Islamic boarding schools, this study also offers strategic recommendations. Among the study's advantages are the advancement of scientific knowledge in the area of educational technology and the enhancement of digital-based learning strategies for educational institutions, instructors, and learners. As a result, this study supports initiatives to modify Islamic boarding schools to meet the needs of modern, digital education.